PENGARUH KOMPENSASI, LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA SERTA DAMPAKNYA PADA KINERJA KARYAWAN PT BANK RAKYAT INDONESIA CABANG BEKASI - Yolanda dan Mariati Simanjorang (Jurnal Manajemen FE-UB, 2016)
Employee performance is the work of employees in carrying out tasks in accordance with the responsibilities charged to all employees. Compensation and work environment is believed to affect work motivation and employee performance. PT. Bank Rakyat Indonesia Bekasi Branch in achieving its intended purpose. The higher the compensation and increased work environment and motivation, the higher the performance of employees of PT. Bank Rakyat Indonesia Bekasi Branch. The purpose of this study is to determine whether the compensation and work environment have a direct significant influence on employee motivation and performance. This research was conducted by taking samples of 60 respondents. Data were collected using questionnaires in the form of a list of statements. Pursuant to result of path analysis, proven that compensation and work environment have positive and significant effect directly to work motivation and employee performance of PT. Bank Rakyat Indonesia Branch Bekasi. Keywords: Compensation, Working Environment, Motivation, Employee Performance.